Variability, correlation and path analysis in pumpkin (Cucurbita moschata L.) (Bangladesh Journal of Agricultural Research, 2015)
Twenty one genotypes of pumpkin (Cucurbita moschata L.) were evaluated to measure the variability among the genotypes for several characters, estimate genetic parameters, association among the characters and their contribution to yield. There was a great deal of significant variation for all the characters among the genotypes. High variability was observed in number of female flowers/plant, number of male flowers/plant, single fruit weight and fruit yield/plant. All the characters except days to first male flowering and days to first female flowering showed high heritability along with high genetic advance in percent of mean. The positive and strong association of number of female flowers/plant (rg=0.918, rp=0.839), number of male flowers/plant (rg=0.687, rp=0.638), fruit length (rg=0.691, rp= 0.520), fruit breadth (rg=0.518, rp=0.420) and single fruit weight (rg=0.492, rp= 0.431) with fruit yield/plant revealed the importance of these characters in determining fruit yield/plant. On the other hand, days to first male flowering (rg = -0.623, rp = -0.550) and days to first female flowering (rg= - 0.689, rp= -0.543) correlated significantly and negatively with fruit yield/plant. The path co-efficient analysis revealed that the highest positive direct effect was recorded in number of female flowers (0.887) to fruit yield and high direct effect was found in case of days to first female flowering (0.798). Fruit breadth was observed to have the highest positive indirect effect (0.899). In case of fruit length (0.381) and single fruit weight (0.398), the significant positive correlation with fruit yield/plant was observed because of the combination of the direct and indirect effects of fruit length and single fruit weight to fruit yield/plant. Overall, the results indicated that days to first female flowering, number of female flowers, fruit length, fruit breadth and single fruit weight can be used as useful selection criteria to increase fruit yield/plant in pumpkin.Bangladesh J. Agril. Res. 40(3): 479-489, September 2015